The Moderation of Frente Farabundo Martí Para La Liberación Nacional’s Economic Orientation in El Salvador, 2009-2019 - Wening, Petrus Putut Pradhopo (Global: Jurnal Politik Internasional, 2020)
Frente Farabundo Martí Para la Liberación Nacional (FMLN) was a Marxist guerrilla group, known for its activities in the 1980s and 1990s to seize El Salvador’s government through war. Post-peace accords, FMLN transformed into an electoral political party and successfully won to lead the government of El Salvador in 2009-2019, but then they compromised their economic policies to suit neoliberalism. This article uses Gill and Law’s conceptualisation of the theory of direct and structural power of capital to explain the causes of FMLN’s neoliberalism-compromising economic policy adjustment in 2009-2019. This article finds that El Salvador’s social and political-economy historical dynamics, which were dominated by the bourgeoisie class since Spain’s colonisation, strengthened transnational capitalists and enabled them to directly penetrate El Salvador’s economy by forming and intervening in political parties, along with dominating the bureaucracy. The combination of these factors caused transnational capitalists to encourage neoliberal reforms which supported the development of the structural power: deindustrialisation, deagrarianisation, and decapitalisation; El Salvador’s economic dependency; dollarisation; and the hegemony of neoliberalism discourses. This article argues that FMLN regime’s economic moderation is caused by the El Salvador bourgeoisies’ strengthened position after neoliberal reforms, allowing them to determine FMLN’s policies through their direct and structural power.